A method for real-time and near non-destructive characterization of metal stress state
Patent Information
- Application Number
- CN202611120341.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-27
AI Technical Summary
该方法有以下缺点:小孔法一般是采用各向同性模型(不考虑微观组织)来反演残余应力
本发明提出的利用服役状态下的压痕尺寸效应与本征的压痕尺寸效应(无应力状态下的压痕尺寸效应)偏离程度来反演服役工件的应力方向(拉伸或压缩)和大小的方法可以现场适用,且实时和近无损评估服役金属的(残余)应力方向(拉伸或压缩)和大小。该发明可对特定工艺制备的工件应力状态做快速检测,从而加速工艺的优化迭代。
Smart Images

Figure CN122982818A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nondestructive testing technology for materials, specifically relating to a method for real-time and near-nondestructive characterization of the stress state of metals. Background Technology
[0002] The stress state of a workpiece in service reflects the existence of interactions such as tension and compression between material micro-elements. This stress characteristic indicates whether the material has the ability to inhibit crack propagation, thus determining the safety of the workpiece in service. Therefore, the stress state of a workpiece in service is of significant indicative importance for judging its service safety. For example, compressive stress parallel to the workpiece surface can inhibit the initiation of potential cracks in that direction, while tensile stress will promote crack propagation in that direction. The magnitude of stress within a workpiece in service varies before crack initiation, during crack initiation, and during crack propagation. Residual stress caused by processes such as welding, additive manufacturing, or rolling, leading to 'inducing cracks,' 'delayed cracking,' and 'strip warping,' remains one of the challenges in industrial control. This invention will provide a solution for measuring these relevant stresses.
[0003] On the other hand, when a workpiece is in service or fully machined, its internal stress is in equilibrium. However, force measurement requires disrupting this stress equilibrium. For example, to measure the magnitude of normal stress at a specific location along a certain direction, a normal stress must be applied at that location along the specified direction, and strain gauges must be attached. Only when the applied normal stress and the original normal stress reach a new equilibrium, or when the strain gauge detects strain, can the magnitude of the normal stress at that location and direction be obtained directly or indirectly through a stress sensor or strain gauge. This is the essence of obtaining tensile stress in tensile tests. This method of measurement, which disrupts the stress equilibrium of the workpiece, cannot meet the requirements of non-destructive testing of stress in service workpieces.
[0004] Currently, commonly used stress measurement techniques for service workpieces, taking residual stress measurement as an example, mainly include (a) destructive or minimally destructive measurement and (b) non-destructive measurement. The former (technique (a)) essentially disrupts the stress balance of the workpiece. The stress state of the workpiece is inverted by calculating the sensitivity of stress to this disruption. For example, the pinhole method. When a hole is drilled, the stress in that area is released. The strain generated by the release is recorded. The residual stress is then inferred based on elastoplastic mechanics. This method has the following disadvantages: the pinhole method generally uses an isotropic model (without considering microstructure) to invert the residual stress. This method has a very large error in stress estimation for materials with strong mechanical anisotropy (strong textured polycrystalline metals or single crystals, etc.). At the same time, the measurement accuracy of destructive methods also depends on the material's sensitivity to strain response to stress release (its essence is measuring the strain after stress release). For metals with high elastic modulus or low strain release coefficient, the requirements for strain measurement accuracy are even higher. The latter (technique (b)) does not disrupt the stress balance, but rather uses the changes in certain physical characteristics of the metal caused by stress changes to indirectly estimate the stress. Examples of non-destructive methods include changes in interplanar spacing (X-ray diffraction), changes in sound velocity (ultrasound), and changes in magnetic domain structure (magnetism). The limitations of non-destructive methods are also quite obvious: they directly measure not force, but stress-sensitive physical quantities. However, these physical quantities are also affected by other factors. For example, the microstructure of metals (including crystallographic texture, phase structure, and internal stress) affects ultrasonic sound velocity, magnetic domain structure, and the measured interplanar spacing. Take the method of characterizing stress through changes in interplanar spacing as an example. X-ray, synchrotron radiation, and neutron diffraction are widely used in engineering. They directly measure interplanar spacing. However, there is currently no practically reliable method for calculating the corresponding stress through changes in interplanar spacing. Current literature and national standards mainly rely on approximate formulas derived from isotropic generalized Hooke's law, which cannot be used for cases with crystallographic texture. For example, rolled metal sheets, extruded bars / plates, forged or wrought metals all have a certain degree of texture. Even if the texture intensity is very small, choosing which diffraction peak to characterize lattice strain for multiphase materials is a practical challenge. The methods described above also require calculating lattice strain, which necessitates knowing the corresponding stress-free interplanar spacing. For welding, the stress-free interplanar spacing differs between the weld and the substrate, and even the heat-affected zone. This increases the difficulty of calculating lattice strain. Furthermore, advanced non-destructive testing methods, such as synchrotron radiation and neutron diffraction, while possessing great penetration depth, require measurements to be performed at synchrotron radiation sources or neutron beamlines, making them unsuitable for field applications. Portable handheld X-ray measuring devices are available for on-site monitoring. However, their measurement depth is generally limited to a maximum of tens of micrometers, making it insufficient for measuring volumetric stress (three-dimensional stress). Summary of the Invention
[0005] In view of the shortcomings of the aforementioned common non-destructive and destructive methods for measuring stress, this invention proposes a method for real-time and near-non-destructive characterization of the stress state of metals.
[0006] The technical solution adopted in this invention is as follows: A method for real-time and near-non-destructive characterization of the stress state of a metal includes the following steps: Measure the intrinsic indentation size effect data at the micrometer scale of in service metallic materials under conditions of no macro-stress and no residual stress; The material parameters of the multi-scale model were verified using intrinsic indentation size effect data. Micrometer-scale indentations are prepared on the surface of in-service metal workpieces to obtain indentation size effect data under service conditions; Based on the indentation size effect data under service conditions, the magnitude and direction of stress in the metal workpiece are obtained by inversion through a multi-scale model.
[0007] Furthermore, the intrinsic indentation size effect data and the indentation size effect data under service conditions include hardness and indentation size.
[0008] Furthermore, the preparation of micron-scale indentations on the surface of the in-service metal workpiece includes: applying static loads of different sizes to the surface of the metal workpiece using a diamond square pyramid indenter, thereby preparing a series of micro-pits of different sizes without affecting the safety of the workpiece during service.
[0009] Furthermore, the number of micropits is at least four, and the depth of the micropits is no greater than 50 micrometers.
[0010] Furthermore, the step of obtaining the magnitude and direction of stress within the metal workpiece through multi-scale model inversion includes: performing indentation simulation using the preset internal stress of the multi-scale model and calculating the hardness and indentation size; adjusting the preset internal stress of the multi-scale model to ensure that the calculated hardness and indentation size data are consistent with the indentation size effect data measured under service conditions. At this point, the preset internal stress of the multi-scale model is an accurate estimate of the stress direction and magnitude within the service metal workpiece.
[0011] Furthermore, a reversible mechanoluminescent material is filled into the micro-pit, and the stress state change of the service metal workpiece at the pit position is monitored in real time through the reversible mechanoluminescent material.
[0012] Furthermore, the real-time monitoring of stress state changes at the indentation location of the in-service metal workpiece using reversible mechanoluminescent materials includes: During the service life of metal workpieces, the luminescence signal of the reversible mechanoluminescent material in the micro-pit is monitored in real time. The degree of stress state change in the metal workpiece is determined by the change in the luminescence signal. If the degree of stress state change is less than the critical value, the luminescence signal of the reversible mechanoluminescent material in the micro-pit is monitored. If the degree of stress state change exceeds the critical value, a micrometer-scale indentation is prepared at the new position of the metal workpiece to obtain the indentation size effect data after the change in service stress state. The magnitude and direction of the stress after the change in stress state are accurately calculated by inversion through a multi-scale model.
[0013] Furthermore, the reversible mechanoluminescent material comprises inorganic mechanoluminescent powder and an adhesive for attaching it to the inner wall of the micropit.
[0014] The beneficial effects of this invention are as follows: The method proposed in this invention, which utilizes the deviation between the indentation size effect under service conditions and the intrinsic indentation size effect (indentation size effect under stress-free conditions) to invert the stress direction (tension or compression) and magnitude of a service workpiece, is applicable in the field and provides real-time and near-non-destructive evaluation of the (residual) stress direction (tension or compression) and magnitude of service metal. This invention enables rapid detection of the stress state of workpieces prepared by specific processes, thereby accelerating process optimization and iteration.
[0015] On the other hand, after each indentation characterization of stress state (magnitude and direction), this invention fills the indentation with a pressure-sensitive material (mechanical luminescent material or mechanical color-changing material) for real-time monitoring of whether the stress state of the workpiece changes during subsequent service. The pressure-sensitive material referred to here is a material whose luminescence intensity or wavelength changes under pressure. Attached Figure Description
[0016] Figure 1 Here are schematic diagrams of hardness measurement and the evolution of key variables: (a) Schematic diagram; (b) Indentation size effect: the relationship between hardness and indentation depth; (c) The relationship between load and indentation depth.
[0017] Figure 2 This is a diagram illustrating the implementation steps of the present invention.
[0018] Figure 3 The experimental and model calculation results of the influence of residual stress on the indentation size effect of 300M steel are as follows: (a) Experimental data (symbols) of the indentation size effect in the quenched and stress-free states can be reconstructed by the multi-scale model (lines); (b) The peak position change (symbols) of the martensite 110 diffraction peak of the quenched sample after heating and cooling, obtained by neutron diffraction measurement, and the multi-scale model reconstruction (lines); (c) Schematic diagram of the multi-scale model. Detailed Implementation
[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0020] This invention utilizes an advanced crystal plasticity finite element model and neutron diffraction experiments to characterize the indentation size effect of metals, revealing that the indentation size effect is sensitive to stress state, or in other words, the stress obtained by dividing the force used in Vickers hardness measurement by the maximum cross-sectional area corresponding to the indentation depth. Figure 1 As shown in Figure a), the indentation size effect is sensitive to stress. This sensitivity can be used to quantitatively invert the direction (tension or compression, etc.) and magnitude of internal stress in a metal. The so-called indentation size effect refers to the fact that, in the depth range of hundreds of nanometers to tens of micrometers, as the indentation depth or pressure load increases, the pressure (or hardness) per unit area gradually decreases, and then tends to a constant value (e.g., ...). Figure 1 (As shown in b). The literature widely uses the evolution of the so-called geometrically necessary dislocation density relative to the statistical dislocation density to explain this phenomenon. This invention uses an indentation depth much larger than the depth at which the influence of geometrically necessary dislocations dominates. Utilizing the sensitivity of the indentation size effect to the stress state, a multi-scale model is used to invert the stress state within the workpiece.
[0021] The core concept of this invention is to first measure the relationship between hardness H0 and indentation depth h0 of a workpiece under stress-free conditions (no macroscopic stress and no residual stress). This data is used for verifying multi-scale model parameters and reflects the intrinsic indentation size effect under stress-free conditions. Taking Vickers hardness measurement as an example, a series of indentations are introduced on the workpiece surface, such as 1 kg, 500 g, 300 g, 100 g, 50 g, and 20 g forces. Then, the diagonal length of the indentation is measured. Combined with the geometry of the indenter, the corresponding cross-sectional area and indentation depth can be calculated, thereby calculating the hardness (H0). Figure 1(a) Note that the indentation size effect reported in the literature is generally below 1 micrometer. However, the indentation depth introduced in this invention is 3-50 micrometers, far exceeding the indentation size effect caused by geometrically necessary dislocations. This invention characterizes the sensitivity of stress to the indentation size effect over a larger depth range. After the workpiece has been in service, residual stress exists within it, and a series of hardness data (Hh) under different forces are measured. The indentation size effect data at this time will deviate from the intrinsic indentation size effect of the workpiece (the intrinsic indentation size effect refers to the indentation size effect obtained under stress-free conditions: H0-h0). To address this deviation, the magnitude and direction of the (residual) stress within the metal workpiece can be inverted using an advanced multi-scale model. Note that the multi-scale model here refers to a computational model that considers the evolution of the microstructure of the metal workpiece. This computational model uses microstructure information obtained by means of XRD or EBSD as input. Through the above steps, the current stress state of the workpiece can be obtained. On the other hand, for pressure-sensitive materials, the "stress-fluorescence signal" data of the pressure-sensitive material used is first measured as a reference for subsequent data evaluation. A reversible mechanoluminescent material is filled into the micro-pits introduced by the previous indentation measurement. During the workpiece's service life, the stress state at these micro-pit locations is monitored in real time to determine whether there are any changes. By observing the changes in the light signal of the material within the micro-pits in real time, the degree of stress state change in the workpiece is qualitatively judged.
[0022] This invention provides a method for real-time and near-non-destructive characterization of the stress state of metals. This method quantitatively assesses and monitors the magnitude and direction of stress in metal workpieces during service. Furthermore, the method is simple to operate, meets the needs of field application, and is also a near-non-destructive testing method. The implementation process of this method is as follows: Figure 2 As shown, the specific steps include: Step A: Acquisition of indentation hardness and size data under stress-free conditions. Using the same material as the workpiece, after stress-relief annealing, measure the indentation size effect data (H0-h0) under stress-free conditions. Specifically, a diamond square pyramid indenter (136° angle between opposite faces) can be used to apply static loads at different locations, similar to Vickers hardness measurement. Select at least four different static loads (e.g., 20g, 50g, 100g, etc.) to prepare a series of indentations of different sizes. The depth of these indentations should be within 50 micrometers, preferably 3-50 micrometers. The data can be obtained as at least four data points on a two-dimensional graph with indentation depth h0 on the horizontal axis and hardness H0 on the vertical axis. This data is used for parameter verification of the multi-scale model and provides a reference for the indentation size effect data (Hh) measured during the subsequent service life of the workpiece.
[0023] Step B: Multi-scale model parameter verification. An advanced multi-scale model is established and the material microstructure is reconstructed. The model parameters are verified using the intrinsic indentation size effect data under stress-free conditions obtained in Step A.
[0024] Step C: Obtaining hardness and indentation size data of the workpiece in service. On the surface of the workpiece in service, select a suitable location and, similar to Step A, perform Vickers hardness measurement to obtain at least four data points showing the relationship between hardness (H) and indentation depth (h).
[0025] Step D: Inversion of stress magnitude and direction. In the model, the residual stress σ inside the material is preset. 11 , σ 22 ,σ 33 The numerical range of this stress cannot exceed the yield stress of the material. By using the least squares method with boundary constraints, the model is run multiple times until the calculated indentation size data under the preset stress state is consistent with the data measured in step C. At this point, the preset stress σ used in the model is... 11 , σ 22 , σ 33 It refers to the accurate estimation of the internal stress of a workpiece.
[0026] Step E: Measurement of the stress-fluorescence signal relationship of the mesoluminescent material. Mesoluminescent inorganic powder + binder was selected as the micro-pit filling material. (a) Inorganic powder: Inorganic crystal powder doped with luminescent ions is selected as the mechanoluminescent functional phase, including but not limited to rare earth doped inorganic fluorescent materials and transition metal ion doped oxide fluorescent materials.
[0027] (b) Binder: Used to solidify and adhere the inorganic powder to the inner wall of the micro-pit. Organic binders may be used, and their selection should take into account the thermal expansion compatibility with the metal substrate, temperature resistance, and chemical compatibility with the inorganic powder.
[0028] (c) Mixing method: Inorganic powder and binder are mixed in a certain proportion to form a paste or slurry, which is then cured by heating or adding a curing agent.
[0029] A compression experiment was conducted on the solidified mechanoluminescent material block to obtain the stress-fluorescence signal relationship, which can be used as an evaluation reference for subsequent real-time detection of stress changes.
[0030] Step F: Filling with metronic light-emitting material. The paste or slurry-like metronic light-emitting material prepared in step E is filled into the indentation corresponding to step C, and then cured and molded.
[0031] Step G: Real-time monitoring. During the service life of the metal workpiece, the emission signal of the optical pressure-sensitive material within the micro-pit is detected in real time. Common methods for detecting fluorescence signals include: (a) CCD / CMOS camera, acquiring a two-dimensional fluorescence intensity distribution image of the array; (b) miniature fiber optic spectrometer / fluorescence spectrometer, capturing the fluorescence spectrum and analyzing its wavelength and fluorescence intensity.
[0032] It should be noted that some mechanoluminescent materials require pre-irradiation with an ultraviolet light source to exhibit mechanochromic behavior. For these types of mechanoluminescent materials, the filling material within the micro-pits should be irradiated with an ultraviolet light source before detecting the fluorescence signal.
[0033] Step H: Determining Stress State Changes. Based on the degree of change in fluorescence signal obtained in Step G, and combined with the stress-fluorescence signal relationship curve obtained in Step E, a preliminary judgment is made. If the assessed stress change is less than 3% of the yield strength, then Step G is continued. If the change exceeds 3% of the yield strength, steps C and D are repeated at a new location to quantitatively invert the new stress state and magnitude of the workpiece. If the stress within the workpiece is less than 70% of the material's yield strength, it is considered safe, and steps F and G are repeated; otherwise, a workpiece failure warning is issued.
[0034] The innovation of this invention is: 1) Utilizing the sensitivity of indentation size effect to force to inverse stress state (magnitude and direction). For metallic materials, the indentation size effect is prevalent. Based on the inventors' recent extensive multi-scale calculations and experimental characterizations, the indentation size effect of metallic materials deviates from its intrinsic behavior (indentation size effect under stress-free conditions) due to the influence of stress state. This deviation is a function of stress; therefore, stress can be inversely derived using a multi-scale model based on the degree of deviation. Compared to patents CN 108387470 A, CN 111649858 B, and CN 113188890 B, this invention, on the one hand, is based on the sensitivity of the relationship between hardness and indentation depth to force (…). Figure 1 (b) in the text, while existing patents utilize the relationship between load and indentation depth ( Figure 1 (c) The former is more sensitive to stress within the metal.
[0035] 2) The biggest difference between this invention and existing patents (CN 108387470 A, CN 111649858 B, CN 113188890 B) is that this invention considers the microstructure of the material, while the three existing patents do not. Only by considering the microstructure can the sensitivity of the relationship between hardness and indentation depth to force be discovered.
[0036] 3) The pressure-sensitive material of the present invention is filled in the indentation and qualitatively monitors the change of stress at that point in real time.
[0037] The differences between this invention and existing patents are as follows: This invention includes (a) quantitative characterization of stress direction (tension or compression) and magnitude, and (b) real-time qualitative monitoring of stress state changes. In existing patents, CN108387470 A uses load-depth curves (see...) Figure 1c) establishes expressions for the macroscopic mechanical properties of metals to evaluate residual stress, neglecting the tensor properties of residual stress (6 independent variables). This invention, however, is based on the relationship between hardness and indentation depth (indentation size effect, see c). Figure 1 (b) Simultaneously, consider the tensor properties of stress. Note the relationship between load and indentation depth ( Figure 1 c) and the relationship between hardness and indentation depth ( Figure 1 b) is completely different. For example, when the indentation depth is zero, the load is zero, while the hardness is much greater than zero. CN111649858B and CN113188890B use nanoindentation testing to evaluate residual stress. They are based on nanoindentation testing and still rely on the relationship between load and indentation depth ( Figure 1 c) Residual stress assessment. First, this invention is based on micrometer-scale indentation measurement. Nanoindentation requires specialized precision instruments, while this invention only requires a common Vickers hardness tester. Second, the most crucial difference between this invention and the three patents mentioned above is that the calculations involved in the three patents do not consider the microstructure. A significant source of residual stress is the non-uniform deformation at the microstructure scale. Only by considering the microstructure can the sensitivity of the indentation size effect to stress be discovered. Explanations of the indentation size effect in the literature are all based on the so-called geometrically necessary dislocation density. In fact, the indentation size effect is sensitive to stress, and the indentation depth used in this invention is much greater than the depth dominated by geometrically necessary dislocations (less than 1 micrometer). This is the core of this invention. To reiterate, this invention is based on the relationship between hardness and indentation depth ( Figure 1 (b) and the load-indentation depth relationship relied upon by the above three patents ( Figure 1 c) is completely different. The load changes from zero with the indentation depth, while hardness is a physical quantity that reflects the mechanical characteristics of metals and is always much greater than zero.
[0038] In addition, the basic principle of the existing real-time stress monitoring schemes (CN111442862A, CN120352057A) is as follows. A mechanoluminescent coating is coated on the surface of a metal structure. When the metal substrate deforms, the coating attached to its surface is deformed by the force, triggering a mechanoluminescent response of the coating. By observing the change in fluorescence intensity, the degree of surface deformation of the metal structure can be qualitatively judged. The differences between the present invention and them are as follows. (1) The information given by the intensity of mechanoluminescence is a scalar and cannot provide the direction of stress. The stress state obtained by the present invention through multi-scale model inversion includes both magnitude and direction of stress. (2) The present invention adopts a structure in which mechanoluminescent material is filled into the pit on the metal surface. The filling material is three-dimensionally constrained by the pit wall, which amplifies the "mechanical interlocking" effect and improves the adhesion reliability of the sensing unit. The existing patents continuously cover the surface of the metal workpiece with a coating. The fluorescence signals of adjacent areas in the continuous coating affect each other, the spatial resolution is limited, and it is difficult to accurately distinguish the information of multiple stress concentration points that are close to each other. (3) The above-mentioned mechanoluminescent coating may conflict with the coating effect of the workpiece itself, which complicates stress analysis and detection. The present invention does not have similar problems. The present invention can be used on coated metal workpieces.
[0039] The beneficial effects of the present invention will be analyzed in detail below: The beneficial effects of this invention are illustrated using 300M high-strength steel as an example. The residual stress after quenching is a key factor in process control. The measurement results of the indentation size effect of this material in the annealed state (approximately stress-free state) and after quenching are as follows: Figure 3 As shown in 'a', different symbols represent experimental measurement data, and lines represent the results of multi-scale model inversion calculations. It can be seen that quenching leads to an increase in material hardness. Simultaneously, the indentation size effect is significantly different from that in the annealed state. Through multi-scale model calculations, the difference in indentation size effect between these two states (the indentation size effect in the annealed state is the intrinsic indentation size effect under no stress) is mainly caused by residual stress. Note that the microstructure in both states is almost entirely martensite. The multi-scale model shows that the residual stress within the material is predominantly triaxial tensile, with the maximum tensile stress being 80% of the material's yield strength. This residual stress value is extremely high, to the point that quenched samples fracture before reaching the yield point during tensile testing, and even surface cracks appear after quenching. Moreover, the fracture stress is approximately 500 MPa, far below its macroscopic yield point. To determine the reliability of the conclusions, Figure 3In the figure, 'b' represents the change in the peak position of the martensitic 110 diffraction peak with temperature during the heating and cooling process of the quenched sample, as measured by neutron diffraction. Here, the peak position corresponds to the interplanar spacing. It can be seen that the coefficient of thermal expansion differs after heating and cooling, reflecting the release of residual stress after heating. Simultaneously, this change in interplanar spacing caused by residual stress during the heating-cooling process can also be reconstructed using a multi-scale model. This further verifies the reliability of the multi-scale model conclusions. It can be observed that the residual tensile stress is released after quenching, so the interplanar spacing decreases after heating and cooling. This change is further verified by thermal expansion experiments. Figure 3 In the figure, 'c' represents the multi-scale model used. The model contains 1000 grains. The testing method of this invention has been verified and is applicable to other metallic materials, such as commercial aluminum alloys and brass.
[0040] Based on the above analysis of beneficial effects, it is confirmed that the technical solution of the present invention can solve the set technical problem, achieve the purpose of the invention, and produce beneficial technical effects, thereby supporting the inventiveness of the invention.
[0041] For residual stress-induced cracks, delayed cracking, and slab warping caused by processes such as welding, additive manufacturing, or rolling, this invention will provide a solution for measuring the relevant stresses.
[0042] Other embodiments of the present invention: For step A, if it is difficult to prepare a sample in a stress-free state, the relationship between the workpiece's hardness and indentation depth before service can be equivalently treated as the intrinsic hardness and indentation depth relationship under stress-free conditions. This can then be used for the multi-scale model parameter verification in step B. Meanwhile, the indenter geometry can also be selected from other forms such as a sphere.
[0043] For the mechanoluminescent material in step E, other binder-free material systems can be used instead of the inorganic material + binder system. For example, TPE-4N can be dissolved in a volatile solvent such as chloroform and dropped into micropits. After the solvent evaporates, TPE-4N remains directly in the pits as a solid crystal / film. If this approach is chosen, the stress-fluorescence signal relationship can be measured by coating it onto a metal surface.
[0044] For the stress safety status determination in step H, users can choose a more "conservative" or more "aggressive" quantitative assessment. This depends on the specific service conditions of the workpiece.
[0045] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and to implement it accordingly. Those skilled in the art will understand that various substitutions, changes, and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the content disclosed in the embodiments of this specification; the scope of protection of the present invention is defined by the claims.
Claims
1. A method for real-time and near-non-destructive characterization of the stress state of a metal, characterized in that, Includes the following steps: Measure the intrinsic indentation size effect data at the micrometer scale of in service metallic materials under conditions of no macro-stress and no residual stress; The material parameters of the multi-scale model were verified using intrinsic indentation size effect data. Micrometer-scale indentations are prepared on the surface of in-service metal workpieces to obtain indentation size effect data under service conditions; Based on the indentation size effect data under service conditions, the magnitude and direction of stress in the metal workpiece are obtained by inversion through a multi-scale model.
2. The method according to claim 1, characterized in that, The intrinsic indentation size effect data and the indentation size effect data under service conditions include hardness and indentation size.
3. The method according to claim 1, characterized in that, The method of preparing micron-scale indentations on the surface of a metal workpiece includes: applying static loads of different magnitudes to the surface of the metal workpiece using a diamond square pyramid indenter, thereby preparing a series of micro-pits of different sizes without affecting the safety of the workpiece during service.
4. The method according to claim 3, characterized in that, The number of micropits is at least four, and the depth of each micropit is no more than 50 micrometers.
5. The method according to claim 1, characterized in that, The process of obtaining the magnitude and direction of stress within a metal workpiece through multi-scale model inversion includes: performing indentation simulation using a preset internal stress in the multi-scale model and calculating hardness and indentation size; adjusting the preset internal stress in the multi-scale model to ensure that the calculated hardness and indentation size data are consistent with the indentation size effect data measured under service conditions. At this point, the preset internal stress in the multi-scale model is an accurate estimate of the stress direction and magnitude within the service metal workpiece.
6. The method according to claim 1, characterized in that, A reversible mechanoluminescent material is filled into the micro-pit, and the stress state change of the metal workpiece at the pit location is monitored in real time through the reversible mechanoluminescent material.
7. The method according to claim 6, characterized in that, The method of real-time monitoring of stress state changes at the indentation location of a service metal workpiece using reversible mechanoluminescent materials includes: During the service life of metal workpieces, the luminescence signal of the reversible mechanoluminescent material in the micro-pit is monitored in real time. The degree of stress state change in the metal workpiece is determined by the change in the luminescence signal. If the degree of stress state change is less than the critical value, the luminescence signal of the reversible mechanoluminescent material in the micro-pit is monitored. If the degree of stress state change exceeds the critical value, a micrometer-scale indentation is prepared at the new position of the metal workpiece to obtain the indentation size effect data after the change in service stress state. The magnitude and direction of the stress after the change in stress state are accurately calculated by inversion through a multi-scale model.
8. The method according to claim 6, characterized in that, The reversible mechanoluminescent material comprises inorganic mechanoluminescent powder and an adhesive for attaching it to the inner wall of the micropit.
Citation Information
Patent Citations
Method for measuring residue stress and metal material elastic-plastic mechanical property by continuous press mark method
CN108387470A
Dynamic stress monitoring method for an aluminum alloy structural member
CN111442862A
A method and system for testing residual stress and triaxial stress in materials using nanoindentation
CN111649858B
A method for measuring residual stress on material surface using nanoindentation technology
CN113188890B
Building stress change measuring method based on optical pressure sensitive coating
CN120352057A